2017
DOI: 10.20944/preprints201703.0222.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production of Bioethanol from Agricultural Wastes Using Residual Thermal Energy of a Cogeneration Plant in the Distillation Phase

Abstract: Alcoholic fermentations were performed adapting the technology to exploit the residual thermal energy (hot water at 83-85°C) of a cogeneration plant and to valorize agricultural wastes. Substrates were apple, kiwifruit and peaches wastes and Corn Threshing Residue (CTR). Saccharomyces bayanus was chosen as biocatalyst. The fruits, fresh or blanched, were mashed; CTR was gelatinized and liquefied by adding Liquozyme® SC DS (Novozyme); saccharification simultaneous to fermentation was carried out using the enzym… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…After the blanching treatment after the pasteurization, only few components were found and a high quantity of ethanol was expressed. The high percentage of ethanol in blanched or pasteurized samples before the application of the homogenization process (BM, BU, PM, PU, PMd and PUd) could be justified by the heating induction of an accelerated fermentation process during the next grinding process [ 27 ]. Methyl acetate, ethyl butanoate, 2–hydroxy propanamide, methyl and ethyl hexanoate had completely disappeared after the thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…After the blanching treatment after the pasteurization, only few components were found and a high quantity of ethanol was expressed. The high percentage of ethanol in blanched or pasteurized samples before the application of the homogenization process (BM, BU, PM, PU, PMd and PUd) could be justified by the heating induction of an accelerated fermentation process during the next grinding process [ 27 ]. Methyl acetate, ethyl butanoate, 2–hydroxy propanamide, methyl and ethyl hexanoate had completely disappeared after the thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Food fermentation basically involves the chemical transformation of complex organic compounds into simpler compounds by the action of enzymes and microorganisms, which has been reported since ancient times as a means of food preservation [1]. A more recent application of the fermentation technique has been applied to the production and extraction of bioactive compounds in the food, chemical, and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…It is comparably high with the current findings on ethanol production from mango (32% v/v). Cutzu and Bardi [36], reported that (substrates were apple, kiwifruit, and peaches wastes; and corn threshing residue) vacuum simple batch distillation by rotary evaporation at lab scale at 80°C (heating bath) and 200 mbar or 400 mbar allowed to recover 93.35% (v/v) and 89.59% (v/v) of ethanol, respectively.…”
Section: Estimation Of Bioethanol From Some Local Over-ripen Mango Varietiesmentioning
confidence: 99%